Characterization and Expression Analysis of a Serine Acetyltransferase Gene Family Involved in a Key Step of the Sulfur Assimilation Pathway in Arabidopsis - Cintia Goulart Kawashima; Oliver Berkowitz; Hell, Ruediger; Noji, Masaaki; Saito, Kazuki (Plant physiology (Bethesda), 2005)
Ser acetyltransferase (SATase; EC 2.3.1.30) catalyzes the formation of O-acetyl-Ser from L-Ser and acetyl-CoA, leading to synthesis of Cys. According to its position at the decisive junction of the pathways of sulfur assimilation and amino acid metabolism, SATases are subject to regulatory mechanisms to control the flux of Cys synthesis. In Arabidopsis (Arabidopsis thaliana) there are five genes encoding SATase-like proteins. Two isoforms, Serat3;1 and Serat3;2, were characterized with respect to their enzymatic properties, feedback inhibition by L-Cys, and subcellular localization. Functional identity of Serat3;1 and Serat3;2 was established by complementation of a SATase-deficient mutant of Escherichia coli. Cytosolic localization of Serat3;1 and Serat3;2 was confirmed by using fusion construct with the green fluorescent protein. Recombinant Serat3;1 was not inhibited by L-Cys, while Serat3;2 was a strongly feedback-inhibited isoform. Quantification of expression patterns indicated that Serat2;1 is the dominant form expressed in most tissues examined, followed by Serat1;1 and Serat2;2. Although Serat3;1 and Serat3;2 were expressed weakly in most tissues, Serat3;2 expression was significantly induced under sulfur deficiency and cadmium stress as well as during generative developmental stages, implying that Serat3;1 and Serat3;2 have specific roles when plants are subjected to distinct conditions. Transgenic Arabidopsis plants expressing the green fluorescent protein under the control of the five promoters indicated that, in all Serat genes, the expression was predominantly localized in the vascular system, notably in the phloem. These results demonstrate that Arabidopsis employs a complex array of compartment-specific SATase isoforms with distinct enzymatic properties and expression patterns to ensure the provision of Cys in response to developmental and environmental changes.